Acute responses of high-intensity circuit training in women: Low physical fitness levels show higher muscle damage - Aline Bianca Alves Nasci; Rafael Bueno Orcy; Léo Dutra Cabistany; Andressa Formalioni; Fabrício Boscolo Del Vecchio (Revista Brasileira de Cineantropometria e Desempenho Humano)
High-intensity intermittent exercise (HIIE) elicits large improvements in health and cardiorespiratory fitness (CRF). HIIE can be applied with calisthenics exercises to improve strength and endurance. The acute effects of high-intensity circuit training (HICT) considering different CRF on myological variables are unknown. The aim was measure acute effects of HICT in young women considering different levels of CRF. Twelve women were allocated in two groups, who achieve 41mLO2•kg-1•min-1 or more= High Physical Fitness (HPF, n=5) and who achieve less than 41mLO2•kg-1•min-1= Low Physical Fitness (LPF,n=7). Protocol: 2x4 sets of 20 seconds at maximum intensity (all-out fashion) interspersed with 10 seconds of passive rest (jumping jacks, squat and thrust using 2kg dumbbells, mountain climber, and burpees). Blood samples were collected before, immediately after, 15minutes, 30minutes, one hour and 24 hours after. Heart rate, serum myoglobin, lactate, and creatine kinase (CK) concentration were analyzed. The HR achieved 94.1±3.7% of HRmax for LPF and 104.5±20.3% for HPF, p=0.03. The mean of delta lactate was similar between groups. The highest myoglobin has reached at 1h after the exercise protocol, with 50.0±30.2 ng/mL for LPF and 36.9±9.25 ng/mL for HPF. The delta of total CK before and after the exercise protocol shows that the serum CK level in LPF was significantly higher than HPF group (p=0.042). HICT composed by calisthenic protocol produced elevated and similar effects on HRmax, serum lactate and myoglobin in the woman with HPF and LPF. However, LPF group presented higher muscle damage inferred by serum CK concentrations.